Integration of Strengthening Islamic Education in Digital Literacy-Based Learning for Junior High School Students - Zarkasi, Fatiya Rahma; Aziz, Jamil Abdul (Lembaga Teewan Journal Solutions, 2026)
This study aims to describe the integration of Islamic Religious Education (IRE) reinforcement in digital literacy-based learning among junior high school students. This study uses a qualitative approach with a descriptive research type. The research subjects are Islamic Religious Education teachers as the main informants, with school principals and students as supporting informants. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, while data validity was maintained through source and technique triangulation. The results show that the integration of digital literacy in PAI learning is carried out through the use of digital media, online learning platforms, and interactive Islamic content. This integration has a positive impact on increasing learning motivation, understanding Islamic values, and shaping students' religious attitudes and digital ethics. Despite challenges such as limited facilities and digital literacy skills, teachers' efforts to develop adaptive learning strategies make digital literacy an effective means of strengthening Islamic values in the digital age.